Design of phononic crystal for enhancing low-frequency sound absorption in mufflers - Yang Bai; Yuehua Chen; Jiahui Zheng (Scientific Reports)
Abstract To enhance the low-frequency sound absorption capabilities of expansion chamber mufflers, a novel Helmholtz-ring phononic crystal cell was developed. This innovative design integrates ring Helmholtz resonators as the phononic crystal scatterer, which is periodically arranged within the expansion chamber of a muffler to achieve enhanced sound attenuation at deep sub-wavelength scales. The transmission loss characteristics of the phononic crystal muffler were thoroughly examined and found to reveal a pronounced enhancement in sound absorption within the low-frequency bandgap. A critical aspect of this study was the analysis of the influence of defect states on transmission loss of the muffler. The introduction of defect states significantly expanded the sound attenuation bandwidth, effectively compensating for reduced sound absorption performance of the muffler outside the bandgap. The proposed phononic crystal muffler demonstrated a marked improvement in both transmission loss and aerodynamic performance compared to the traditional expansion chamber muffler. Notably, the sound attenuation was further augmented when in defective states. Corresponding experimental investigations were conducted and confirmed the effectiveness of the phononic crystal muffler within its designated bandgap range. This research presents a new way for the development of more efficient noise control solutions.